Leader approach: An opportunity for rural development - Adrian Turek Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The rural development programs that are developed with the active involvement of local citizens have a long tradition in the European Union. From 1991 until 2006, Leader I, Leader II and Leader + have been designed as a laboratory to encourage the emergence and testing of new approaches to integrated and sustainable development, rural development policy in the Community. In this way, the initiative Leader, after had experience in three programming periods, has reached a level of maturity that allowed the competent authorities to implement the Leader approach more widely in national rural development programs. For this reason, Council Regulation no. 1698/2005 of the European Agricultural Fund for Rural Development (EAFRD) for the period 2007-2013, contains a fourth axis called LEADER axis. The main focus of the paper is given to the implementation of LEADER in Romania in the period 2007-2013. The paper has three parts. The first part presents the general characteristics of the LEADER approach and the measures that are performed within the Rural Development Programme 2007-2013. In the second part is presented the list of local action groups and their spatial-demographic characteristics.
Keywords: 330; Rural development; agricultural policy; LEADER approach; Local Action Group; local development strategies